Modes of occurrence and partitioning behavior of trace elements during coal preparation—A case study in Guizhou Province, China. (1st May 2019) - Liu, Cheng; Zhou, Changchun; Zhang, Ningning; Pan, Jinhe; Cao, Shanshan; Tang, Mengcheng; Ji, Wanshun; Hu, Tingting
Highlights: As, Se in coal is more likely to be released into water while Be, Hg is insoluble. Trace elements in coal mainly migrate to and are enrich in gangue, slime, middlings. Over 50% trace elements can be removed by pre-gangue removing at density of 1.8 g/cm 3 . Abstract: Coal preparation technology is expected to play an important role in trace elements removal before coal combustion. The modes of occurrence of five trace elements (As, Se, Pb, Be, and Hg) in two coal cleaning plants in Guizhou, China, designated WJZ and ZZC, were studied using screening and float-and-sink tests. The behaviors of these trace elements when coal was cleaned were also investigated via sampling and analysis of raw coal, coal products, fresh water, and circulating water in two coal cleaning plants. Screening tests show that the content of trace elements is highest in 3–1 mm or 1–0.5 mm size fraction and they distributed mainly (more than 50%) in the +0.5 mm size fractions. Float-and-sink tests indicate that trace elements have a strong inorganic affinity and are significantly enriched, distributed in high-density fraction (+1.8 g/cm 3 ). Over 50% of trace elements could be removed when pre-gangue removal is done with separation density of 1.8 g/cm 3 . The analysis of solid samples (raw coal, coal products) demonstrates that trace elements migrated mainly into gangue, and slime, enrichment of trace elements in middlings was also observed in ZZC plant. Results of water samples analysis suggest that Se, and As in coal are more likely to be released into water during coal cleaning while Be and Hg are present in a highly insoluble form in coal.